Challenges of Economic of Georgia: Good and Bad EconomicGrowth - Kasradze, Tea; Zarnadze, Nino (European Journal of Economics and Business Studies, 2022)
The Georgian economy has been undergoing serious transformations over theyears. The reforms carried out by the government affected all spheres of theeconomy - health care, education, industry, the military-technical complex,etc. The annual growth of the economy is approximately 4.8%. The EU,partner developed countries and donor international organizations allocatehuge financial resources for the implementation of the changes planned bythe government. Despite this, the economy of Georgia is in a difficult situation.The reason of economic stagnation in which the country has been for years isan extensive vector of development of the national economy. Investmentprojects carried out in the country in recent years are extensive in most cases.These projects are aimed at increasing current profits. They mostly are notoriented to long-term perspective. Intensification projects based on scientificand technical progress that are capable to change the level of productionqualitatively are few. Despite the lack of an innovative scientific and technicalbackground the economic indicators are increasing. However, the analysis ofthe indicators’ growth factors shows the lack of development of the nationaleconomic system. The data does not reflect the real economic statement andpoint to an extensive (so-called bad growth) growth of the national economyand will lead to economic and political crisis. The intensive and extensivefactors of economic growth is discussed and analyzed in the paper. Therecommendations and measures are developed by the authors for improvingthe economy through the intensification of production processes.
Keywords: Economic growth; intensive and extensive growth; bad and good growth; innovation development; scientific and technical progress